Study of Judicial Legal Person in Appeal Procedure from District Court to Provincial Court in Thailand. Issue 2 (2nd April 2016) - Marpraneet, Natchai
ABSTRACT: This research on the attitude of lawyers towards cases appealed from the District Court to the Provincial Court comes from a problem of the long-time adjudication timescale of cases in the Court of Appeal. This problem is inconsistent with the intention of establishing a District Court, aimed at adjudicating cases faster. This research employed a quantitative methodology in order to study the attitude of the lawyers involved in the appeals to the District Court and on the appeal process of the Provincial Court. There was a sample group of 313 lawyers, including judges, prosecutors, and attorneys. The research found that the appeal of cases from the District Court to the Provincial Court was a fast track in judging the cases with a small amount of capital and a low rate of criminal penalties. The study showed that about 55.9% did not agree on the possibility of employing the appeals system of the Provincial Court instead of the Court of Appeal. Another 44.1% of the samples were unhappy with the current appeal system. The appeal system of the Provincial Court guarantees the right to due process as declared in Section 27 and 40 on adjudication in the Constitution of the Kingdom of Thailand, B.E. 2550.